The relationship between office type and job satisfaction: Testing a multiple mediation model through ease of interaction and well-being - Tobias Otterbring; Jörg Pareigis; Erik Wästlund; Alexander Makrygiannis; Anton Lindström (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: This cross-sectional study investigated the associations between office type (cellular, shared-room, small open-plan, and medium-sized open-plan) and employees' ease of interaction with coworkers, subjective well-being, and job satisfaction. METHODS: A brief survey including measures of office type, ease of interaction with coworkers, subjective well-being, and job satisfaction was sent electronically to 1500 Swedish real-estate agents, 271 of whom returned usable surveys. The data were analyzed using a regression-based serial multiple mediation model (PROCESS Model 6), which tested whether the relationship between office type and job satisfaction would be mediated by ease of interaction and, in turn, subjective well-being. RESULTS: A negative relationship was found between the number of coworkers sharing an office and employees' job satisfaction. This association was serially mediated by ease of interaction with coworkers and subjective well-being, with employees working in small and medium-sized open-plan offices reporting lower levels of both these aspects than employees who work in either cellular or shared-room offices. CONCLUSIONS: Open-plan offices may have short-term financial benefits, but these benefits may be lower than the costs associated with decreased job satisfaction and well-being. Therefore, decision-makers should consider the impact of office type on employees rather than focusing solely on cost-effective office layout, flexibility, and productivity.